Internationalization of Higher Education and the Future of the Planet - Rumbley, Laura (International Higher Education, 2020)
International mobility, the hallmark activity of internationalization of higher education, relies heavily on air travel, which is contributing directly to the global climate crisis. Commitments to immediate and creative solutions to offset these detrimental environmental effects must be embraced by the international higher education community.